Types Of Farms and Methods of Agriculture At The Karakalpaks (Xix Century) (Zien Journal of Social Sciences and Humanities, 2021)
The article provides information from historical and written sources about the occupation of the Karakalpaks in the 19th century, along with agriculture and animal husbandry. It also marks the sown areas suitable for agriculture and the location of cities and auls, as well as the life of the Karakalpaks.